2017
DOI: 10.1016/j.jvs.2016.07.109
|View full text |Cite
|
Sign up to set email alerts
|

Systematic identification and management of barriers to vascular surgery patient discharge time of day

Abstract: Objectives Length of stay fails to completely capture the clinical and economic effects of patient progression through the phases of inpatient care, such as admission, room placement, procedures, and discharge. Delayed hospital throughput has been linked to increased time spent in the emergency department and post-anesthesia care unit, delayed time to treatment, increased inhospital mortality, decreased patient satisfaction, and lost hospital revenue. We identified barriers to vascular surgery inpatient care p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 40 publications
(49 reference statements)
0
17
0
Order By: Relevance
“…Additionally, the findings of the study are consistent with the results of previous studies discussing the impact of the structured NLR and nurse leader practices on enhancing the coordination of care and the discharge process (Alaloul, Williams, Myers, Jones, & Logsdon, ; McIntosh et al, ). A structured NLR is an opportunity for the nurse manager to ensure that all discharge instructions, education, and coordination of care after discharge are in place before discharge (Eggenberger, Garrison, Hilton, & Giovengo, ; Page et al, ; Sharma et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the findings of the study are consistent with the results of previous studies discussing the impact of the structured NLR and nurse leader practices on enhancing the coordination of care and the discharge process (Alaloul, Williams, Myers, Jones, & Logsdon, ; McIntosh et al, ). A structured NLR is an opportunity for the nurse manager to ensure that all discharge instructions, education, and coordination of care after discharge are in place before discharge (Eggenberger, Garrison, Hilton, & Giovengo, ; Page et al, ; Sharma et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen articles were excluded at this stage for reasons including: minimal number of vascular surgery patients in sample, or lack of readmission data specific to the vascular surgery population ( n = 7); lack of comparison readmission rate ( n = 4), lack of in-hospital or post-discharge intervention ( n = 3), or surgical intervention only ( n = 2). Six studies from these searches were included in the full review (de Mestral et al, 2019; Hornick et al, 2016; Mousa et al, 2019; Reed et al, 2004; Rümenapf et al, 2013; Sharma et al, 2017). A reference search of six potentially relevant secondary reviews identified from the initial search was also performed.…”
Section: Methodsmentioning
confidence: 99%
“…Decreases in average length of stay of 2.8 to 2.9 days was reported in two studies (Aicher et al, 2019;Reed et al, 2004). Interestingly in two studies the length of stay increased slightly post-intervention, but this increase did not reach statistical significance and tapered off over time (Rümenapf et al, 2013;Sharma et al, 2017). While the telehealth intervention by Mousa et al (2019) did not achieve significant readmission rate reduction, participants did report significant improvements in quality-of-life measures (p < .05) and trends toward improved satisfaction (p = .072).…”
Section: Other Notable Outcomesmentioning
confidence: 96%
“…Of the 63.9% (N=101) studies measuring work and team process outcomes (Table 1), all but 1 reported that the huddle had a statistically significant positive impact on frontline staff. 6,8,9,[125][126][127][128][129][130][131][140][141][142][143][144][145][146][147][148]150,[153][154][155][156][157] Of these, studies found evidence for improved efficiency, process-based functioning, and communication across clinical roles (64.4%; N=65); 6,8,9,[125][126][127][140][141][142][143][144][145][153][154][155] improved situational awareness and staff perceptions of safety and safety climate (44.6%; N=45); 6,8,11,26,30,31,…”
Section: Effectiveness Of Huddlesmentioning
confidence: 99%
“…Seventy studies (44.3%) measured clinical care outcomes 1,11,25,27,30,31,34,36,41,[49][50][51]56,63,72,74,86,89,94,97,[99][100][101]128,130,[132][133][134][135][136][137][138][139]141,144,[149][150][151][152]155,[157][158][159][160][161][162][163][164] , of which all reported the huddle had a positive clinical impact. Positive The CUS assertive statements help frontline staff speak up or speak out in uncomfortable situations.…”
Section: Effectiveness Of Huddlesmentioning
confidence: 99%